Violence against women : impacts on women's health derived from a U.S. nationwide study - Stewart, Megan C., 1980- (Criminal justice (LFB Scholarly Publishing LLC), 2014)
Using data from the National Violence Against Women Study (NVAWS) and general strain theory (GST) as a theoretical basis, Stewart explores the impact of the victim-offender relationship on psychological and physical health and wellbeing for the crimes of rape, stalking, and physical assault. She asks two questions: first, what is the prevalence of violence against women by victim-offender relationship? and, second, what is the effect of the victim-offender relationship on health outcomes? Findings indicate that a variety of perpetrators are responsible for violence against women. Additionally,